RISK ASSESSMENT IN 13-STORY BUILDING PROJECTS WITH THE FAILURE MODE AND EFFECT ANALYSIS (FMEA) METHOD AND THE DOMINO EFFECT - Salman Farid Lahmadi; Betanti Ridhosari; I Wayan Koko Suryawan; Ariyanti Sarwono (Jurnal Kesehatan Masyarakat dan Lingkungan Hidup, 2021)
The building construction project is one of the activities that can pose a safety risk. Work safety risk assessment can be done using the Failure Mode and Effect Analysis (FMEA) method and looking at the Risk Priority Number (RPN) value. The purpose of this research is to take a case study of the building Office in determining the highest RPN and provide recommendations on its management. This project consists of 13 earthworks, passenger hoist, tower crane, scaffolding jobs, ironworks, formwork work, foundry work, mechanical, electrical plumbing (MEP) work, welding work, and floor wall doing works, and ceramic installation work. The highest RPN from the observations occurred in Iron Fabrication which can cause fingers hit by a bar cutter and bender. In this case, personal protective equipment (PPE) is significant in preventing these impacts from occurring in the project work area.